IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DALAM MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK - Copy - Badawi Badawi (Universitas Muhammadiyah Surakarta, 2020)
This research aims to describe the implementation of madrasah-based management in enhancing students’ achievement at Madrasah Aliyah Boarding School Nurul Falah Borongganjeng of Bulukumba Regency, South Sulawesi. This research is a qualitative study through a phenomenological approach. The informants in this study are the headmaster, teachers, education personnel, and learners. The data collection technique used are observations, interviews, and documentation. The information obtained is processed and analyzed through several stages including data reduction, data display, and verification or withdrawal of conclusions. The results showed that the implementation of Madrasah-Based Management (MBM) at Madrasah Aliyah Nurul Falah Borongganjeng can improve students’ achievement. Teachers as spearhead education can act autonomously through the application of madrasah-based management by developing approaches, methods, strategies, techniques, media to be used in accordance with the subject matter to be delivered making it easier for learners to understand and ultimately impact on their learning achievements.